The interactions between cGAS-STING pathway and pathogens - Cheng, Zhangliang (Signal Transduct Target Ther, 2020)
Cytosolic DNA is an indicator of pathogen invasion or DNA damage. The cytosolic DNA sensor cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) synthase (cGAS) detects DNA and then mediates downstream immune responses through the molecule stimulator of interferon genes (STING, also known as MITA, MPYS, ERIS and TMEM173). Recent studies focusing on the roles of the cGAS-STING pathway in evolutionary distant species have partly sketched how the mammalian cGAS-STING pathways are shaped and have revealed its evolutionarily conserved mechanism in combating pathogens. Both this pathway and pathogens have developed sophisticated strategies to counteract each other for their survival. Here, we summarise current knowledge on the interactions between the cGAS-STING pathway and pathogens from both evolutionary and mechanistic perspectives. Deeper insight into these interactions might enable us to clarify the pathogenesis of certain infectious diseases and better harness the cGAS-STING pathway for antimicrobial methods.